Authors' reply - anaphylactic shock with methylprednisolone, Kounis syndrome and Hypersitivity to corticosteroids: a clinical paradox - F. Porcaro; M. G. Paglietti; A. Diamanti; F. Petreschi; A. Schiavino; V. Negro; V. Pecora; A. Fiocchi; R. Cutrera (BMC, 2019)
Abstract In our letter, we comment the paper of Kounis et al., that highlights a poor-known clinical entity determined by systemic use of corticosteroids, the so-called "Kounis syndrome type I". We appreciated and shared the intent of Authors to treat the important issue of high risk of adverse drug reaction in patients with atopic diathesis and we confirm the need to administer corticosteroids with caution in patients suffering from allergic disease.